Association between triglyceride glucose-body mass index with all-cause and cardiovascular mortality in adults with osteoporosis: a prospective study - Li, Yuhao; Xie, Xiaowan; Liu, Yazhou; Sun, Haoran; Gong, Zhaoqi; Ding, Wenbo (Frontiers in Endocrinology, 2025)
PurposeThis study aims to examine the relationship between the insulin resistance (IR) biomarker, specifically triglyceride-glucose body mass index (TyG-BMI), and all-cause as well as cardiovascular mortality in patients diagnosed with osteoporosis.MethodsThis study employed a prospective cohort design involving 302 patients diagnosed with osteoporosis, recruited between 2018 and 2020, with follow-up extending until 2024. During this period, occurrences of all-cause mortality (64 cases) and cardiovascular mortality (19 cases) were recorded. A comparative analysis was conducted in conjunction with other insulin resistance indices, including TyG, METS-IR, and TG/HDL-C. Restricted cubic spline and multivariable Cox proportional hazards regression analyses were utilized to elucidate the relationship between the TyG-BMI index and the risk of all-cause and cardiovascular mortality in patients with osteoporosis. Furthermore, subgroup analyses were performed to examine potential interactions and identify subpopulations at elevated risk of mortality.ResultsTyG-BMI is significantly positively correlated with all-cause mortality (for each 1 unit increase, HR = 1.01, 95% CI: 1.00-1.02). Patients in the fourth quartile (Q4) have an almost 2.8-fold increased risk of all-cause mortality compared to those in the first quartile (Q1) (HR = 2.79, 95% CI: 1.16-6.73). The cardiovascular mortality rate is significantly higher in the TyG-BMI Q4 group (HR = 6.33, 95% CI: 1.19-33.80). ROC curve and DeLong test indicate that the predictive capacity of TyG-BMI for all-cause and cardiovascular mortality surpasses that of other insulin resistance indicators. Subgroup analyses further suggest that the risk of cardiovascular mortality is elevated in patients with low HDL, high serum calcium, and elevated creatinine levels.ConclusionThe TyG-BMI index exhibits a linear association with the risk of both all-cause mortality and cardiovascular mortality. Additionally, TyG-BMI functions as an independent predictor of mortality risk in patients with osteoporosis, with elevated values indicating a poorer prognosis. These findings highlight the significant role of IR in the progression of osteoporosis.